2016
DOI: 10.1080/17470218.2015.1115885
|View full text |Cite
|
Sign up to set email alerts
|

The propositional basis of cue-controlled reward seeking

Abstract: Two experiments examined the role of propositional and automatic (ideomotor) processes in cue-elicited responding for rewarding outcomes (beer and chocolate). In a training phase, participants earned either chocolate or beer points by making one of two button-press responses. Rewards were indicated by the presentation of chocolate and beer pictures. On test, each trial began with a picture of beer or chocolate, or a blank screen, and choice of the beer versus chocolate response was assessed in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 49 publications
6
39
0
Order By: Relevance
“…Consistent with prior studies, the Non-Reversal No Load group demonstrated an O-R priming effect, where the reward cues selectively increased the response that predicted the common outcome (e.g., Hogarth, 2012;Martinovic et al, 2014;Seabrooke et al, 2016. Furthermore, an O-R priming effect was observed even under cognitive load.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent with prior studies, the Non-Reversal No Load group demonstrated an O-R priming effect, where the reward cues selectively increased the response that predicted the common outcome (e.g., Hogarth, 2012;Martinovic et al, 2014;Seabrooke et al, 2016. Furthermore, an O-R priming effect was observed even under cognitive load.…”
Section: Discussionsupporting
confidence: 85%
“…throughout the transfer test. We used this instruction to be consisted with our previous work (Seabrooke et al, 2016), where we observed very strong reversal effects. The Load groups also completed a cognitive load task (described below) during the transfer test.…”
Section: Methodsmentioning
confidence: 99%
“…A third theory of PIT is our goal-directed, propositional model (Hogarth et al, 2014;Seabrooke et al, 2016Seabrooke et al, , 2017. Similar to hierarchical theory, participants are assumed to infer that the Pavlovian stimuli signal which outcomes are more available, and therefore which instrumental response is more likely to be reinforced on any given test trial.…”
Section: Discussionmentioning
confidence: 99%
“…To solve this contradiction, a range of secondary processes have been postulated wherein drug seeking becomes less controlled. Theories that appeal to appetitive Pavlovian conditioning, for instance, argue that the pairing of drug cues with drug reward endows drug cues with capacity to elicit drug seeking, and sensitivity to this effect may underpin dependence [1,[17][18][19][20], because cue-reactivity is automatic [21], or because drug cues signal the accessibility (and hence greater utility) of the drug in the presence of drug cues [22,23]. However, drug cue-reactivity is not reliably associated with dependence severity in humans [24][25][26][27], suggesting this mechanism probably does not underpin addiction.…”
Section: Brief Introduction To Theories Of Addictionmentioning
confidence: 99%